1987
DOI: 10.1002/j.1556-6676.1987.tb00781.x
|View full text |Cite
|
Sign up to set email alerts
|

Three Approaches to Research Training in Counseling

Abstract: Three approaches to training counseling students in the processes of research and publication are described. The major difference is in the duration, from a span of several years to one semester to a half‐day workshop. Ideas are presented about working productively within each of those time frames.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Gelso emphasized that the use of these environmental influences can help students develop more positive and productive attitudes toward research. Stone (1986) and Heppner, Gelso, and Dolliver (1987) have argued in support of Gelso's position. In contrast, Holland (1986) viewed personality traits as the main factor contributing to the low research productivity of students and faculty attracted to counseling psychology.…”
mentioning
confidence: 95%
“…Gelso emphasized that the use of these environmental influences can help students develop more positive and productive attitudes toward research. Stone (1986) and Heppner, Gelso, and Dolliver (1987) have argued in support of Gelso's position. In contrast, Holland (1986) viewed personality traits as the main factor contributing to the low research productivity of students and faculty attracted to counseling psychology.…”
mentioning
confidence: 95%
“…Vacc and Loesch (1983) postulated that as technology increases counselors will need research skills that validly and efficiently measure and account for the effectiveness of their attempts to help others. Unfortunately, the majority of counselor education programs present research as an isolated activity, poorly integrated within the curriculum (Galassi, Stoltz, Brooks, & Trexler, 1987;Goldman, 1978;Heppner, Gelso, & Dolliver, 1987;Hoshmand, 1989;Martin & Martin, 1989;Nuttall & Ivey, 1978). As a result, few career counselors engage in research activities, and they do not realize that the purpose of research is to improve practice.…”
Section: The Career Counselor As Scientist-practitionermentioning
confidence: 99%
“…but rather the process bywhich ourprograms attempted to train scientist-practitioners (Gelso. 1993;Heppner et al .• 1987). Investigators have indicated that one key to increasing the research activity generated by counseling professionals is to study and improve the manner in which students are trained to develop as scholars and researchers (Betz, 1986;Gelso, 1979;Gelso et al .• 1988;Krumboltz, 1986;Royalty & Reising.…”
mentioning
confidence: 99%